Monitoring Basic Opportunities throughout the Lifecycle with the Human Opportunity Index in Chile - World Bank (Washington, DC, 2012)
Chile has made significant progress towards equalizing opportunities in recent years, especially those pertaining to poverty alleviation, school enrollment, and access to health services. A monitoring system of basic opportunities that effectively incorporates equity concerns may help policymakers to design better policies for vulnerable groups in Chile. The Human Opportunity Index (HOI) is an equality of opportunity adjusted coverage rate. The HOI provides a tractable way, in a single indicator, to measure progress toward universal coverage of opportunities as well as equitable access to those opportunities. Along with being a simple, intuitive and tractable measure, the HOI also satisfies several properties deemed desirable for an equity measure. Any increase in the amount of opportunities will improve the HOI despite to whom it is allocated. It is pro-vulnerable because if the coverage rate of a vulnerable group increases holding the overall coverage rate constant, the HOI also increases. Similarly, for a given expansion of available services, the HOI increases more if the extra units of services are allocated to a vulnerable group. In general the HOI ranges from 0 to 100. The three main findings that emerge from this initial monitoring exercise are: (i) Chile does well in providing fundamental basic opportunities, but not as well on more advanced indicators such as quality learning, completion of secondary on time, access to some tertiary education, as well as bundles of services for early childhood development, and youth development; (ii) inequality of opportunity in Chile operates mainly on the basis of parental education and location, and (iii) a sound monitoring system of the equitable provision of opportunities for all may help the Chilean society strengthen consensus towards equity and provide policymakers with the right incentives to design and implement better policies to address these issues.